Sound propagation in a two-dimensional Bose gas across the superfluid transition - Vijay Pal Singh; Ludwig Mathey (Physical Review Research, 2020)
Motivated by recent experiments in Ville et al. [Phys. Rev. Lett. 121, 145301 (2018)]PRLTAO0031-900710.1103/PhysRevLett.121.145301, we study sound propagation in a two-dimensional Bose gas across the superfluid-thermal transition using classical-field dynamics. Below the transition temperature we find a Bogoliubov and a non-Bogoliubov mode, and above it we find the normal sound mode and the diffusive mode, as we determine from the dynamical structure factor. Our simulations of the experimental procedure agree with the measured velocities and show that below the transition temperature the measurements detect the Bogoliubov mode. Above the transition, they detect either the normal sound mode for low densities or weak interactions or the diffusive mode for high densities or strong interactions. As a key observation, we discuss the weak-coupling regime in which the non-Bogoliubov mode has a higher velocity than the Bogoliubov mode, in contrast to a hydrodynamic scenario. We propose to detect this regime via step-pulse density perturbation, which simultaneously detects both sound modes.